Quantum oscillations in coupled orbits networks of (BEDT-TTF) salts with tris(oxalato)metallate anions - Laukhin, V.N.; Audouard, Alain; Fortin, Jean-Yves; Vignolles, David; Prokhorova, T.G.; Yagubskii, E.B.; Canadell, Enric (Физика низких температур, 2017)
Band structure calculations relevant to bis-ethylenedithio-tetrathiafulvalene-based charge transfer salts containing tris(oxalato)metallate anions, with generic formula (BEDT-TTF)₄A[M(C₂O₄)₃]·Solv, where A is a monovalent anion, M is a trivalent cation and Solv is a solvent, suggest that their Fermi surface is liable to achieve networks of compensated orbits coupled by magnetic breakdown. Even though this picture accounts for quantum oscillations spectra of a number of these compounds, puzzling results can be noticed in several cases, pointing to the possibility of Fermi surface reconstruction at low temperature.